Development Theory in Sociology: Understanding Paradigms, Modernization, Dependency, and World Systems - Akdila Bulanov; Afri Wandi Zahri Ramadhan; Nabila Sukma; Putri Varisya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article discusses development theory in sociology, encompassing paradigms, modernization, dependency, and world systems. The background to this research is based on a long-standing debate in development studies, demonstrating that socioeconomic change cannot be understood through a single approach. Modernization theory emphasizes internal factors as the cause of underdevelopment and the solution to development, dependency theory critiques the external domination of developed countries over developing nations, while world systems theory views development as part of the interconnected dynamics of the global capitalist system. The purpose of this research is to analyze the basic concepts of each development theory in sociology and understand their implications for social change in society. The method used is a literature study with a qualitative approach through the review of various relevant sources. The results of the study indicate that development paradigms significantly influence perspectives on the causes, processes, and direction of social change. Modernization, dependency, and world systems theories each provide different but complementary explanations for understanding the dynamics of development in developing countries. Through this conceptual review, it can be concluded that development cannot be separated from internal and external relations and must be understood within a broader global framework. This article is expected to serve as a conceptual reference for academics and practitioners in understanding development theory in sociology more comprehensively.